Pengaruh Brand Image, Brand Engagement dan Perceived Value terhadap Intention to Purchase melalui Variabel Trust di Media Sosial Instagram: Studi pada Mahasiswa Magister Manajemen Pascasarjana Universitas Bandar Lampung - Arfina Shella Meilany; Andala Rama Putra Barusman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The development of social media, particularly Instagram, has transformed consumer behavior in the purchasing decision-making process by emphasizing the role of brand perception and trust. This study employs a quantitative approach using a survey method conducted among Master of Management students at Universitas Bandar Lampung who actively use Instagram. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that Brand Image, Brand Engagement, and Perceived Value have a positive and significant effect on Trust, and Trust has a positive effect on Intention to Purchase. Furthermore, Brand Image, Brand Engagement, and Perceived Value also have a direct influence on Intention to Purchase. The indirect effect analysis confirms that Trust acts as a mediating variable in the relationship between Brand Image, Brand Engagement, and Perceived Value and Intention to Purchase. These findings highlight that Trust is a key factor in enhancing consumers’ purchase intention on social media; therefore, digital marketing strategies should focus on strengthening brand image, fostering consumer engagement, and enhancing perceived value.